Stress Analysis of the Hip Bone - Jaffar, Dr. Akram Abood; Abass, Dr. Sadiq Jaffar; Abdullah, Huma Mohamed (Al-Khwarizmi Engineering Journal, 2017)
The bony pelvis has a major role in weight transmission to the lower limbs. The complexities of its geometric form, material properties, and loading conditions render it an open subject to biomechanical analysis. The present study deals with area measurement, and three-dimensional finite element analysis of the hip bone to investigate magnitudes, load direction, and stress distribution under physiological loading conditions. The surface areas of the auricular surface, lunate surface, and symphysis pubis were measured in (35) adult hip bones. A solid model was translated into ANSYS parametric design language to be analyzed by finite element analysis method under different loading conditions.The surface areas of the auricular surface, symphysis pubis, and lunate surface were (14.39±2.05cm², 4.46±1.01cm², and 24.63±3.2cm²) respectively. A significant positive linear relationship was found between the auricular surface area and that of the lunate surface. No such correlation was found between the auricular surface and symphysis pubis. The finite element analysis model showed that stresses, using the Von Mises method, were distributed mainly in the acetabulum (anterior, superior and posterior part: 11.2%, 5.4%, 15.9% respectively), auricular surface 24.6%, and ischial tuberosity 40.3%, when a 70kg load was applied. Stresses calculated for higher loads showed a positive direct proportional increase. Principle stresses indicated that failure occurred in the anterior and posterior surface of the acetabulum as well as in the sacrioiliac joint.